Mathematical modelling and multi-response optimisation using response surface methodology and grey based Taguchi method: an experimental investigation. (1st January 2011) - Sahoo, Ashok Kumar; Sahoo, Bidyadhar
The present study deals with the application of full factorial design of experiment and response surface methodology in developing mathematical model considering input variables, i.e., cutting speed, feed and depth of cut for flank wear and surface roughness when hard turning AISI 4340 steel (HRC 47±1) using multilayer coated carbide insert (TiN/TiCN/Al2 O3 /ZrCN) under dry environment. Mathematical model output concluded that the RSM models proposed are statistically significant and adequate because of higher R 2 value. It shows the high correlation between the experimental and predicted values. From ANOVA table, it is evident that, feed is the significant factor affecting surface roughness followed by cutting speed. Depth of cut is found to be insignificant from the studied range. For flank wear, cutting speed is the most significant factor followed by depth of cut. Feed is found to be insignificant for flank wear. The improvement of grey relational grade from initial parameter combination (d2-f3-v4) to the optimal parameter combination (d4-f1-v3) is found to be 0.4645 and is improved through the approach of Taguchi method with grey relational analysis to optimise the process parameter for multiple performances (surface roughness and flank wear).